Theoretical modeling for interfacial catalysis. (31st March 2021) - Zhou, Lingyun; Zhuo, Lingshu; Yuan, Ruming; Fu, Gang
Abstract: Heterogeneous catalysis is vital in modern chemical industry. The development of next‐generation heterogeneous catalysts demands methodological shift from trial‐and‐error to theory‐guided design. However, heterogeneous catalysis usually involves complex surfaces/interfaces, which make it difficult to establish a reasonable model. Herein, we reviewed the recent progress in our group, and demonstrated a new research paradigm to successfully bridge the material gap between theory and experiment. Accordingly, three important interfacial effects of heterogeneous catalysts have been discussed in detail, that is, the support effect of oxide‐on‐metal catalysts, the coordination effect of atomically dispersed metal catalysts (ADCs) and the ligand effect of molecular modification. We addressed that the close cooperation of theory and experiment is essential to gain deep mechanistic insights and help to optimize heterogeneous catalysts in a more rational way. This article is categorized under: Structure and Mechanism > Reaction Mechanisms and Catalysis Abstract : Complicated interfacial structure of real catalysts.